Assessment of knowledge, attitude, and practice of child caregivers towards oral rehydration salt and zinc for the treatment of diarrhea in under 5 children in Gondar town - Dawit Kumilachew Yimenu; Asmamaw Emagn Kasahun; Mohammed Chane; Yeelshaddai Getachew; Biruktawit Manaye; Zemene Demelash Kifle (Elsevier, 2022)
Background: Diarrhea is the second-largest cause of death in under-five children, killing an estimated seven hundred sixty thousand children in Africa each year. This study aimed to assess the knowledge, attitude & practice of child caregivers towards oral rehydration salt and zinc use for the treatment of diarrhea in under 5 children in Gondar town, Amhara regional state, Ethiopia. Methods: Institutional based cross-sectional study was conducted at the pediatrics outpatient department of the University of Gondar comprehensive specialized hospital. Data was collected using a structured questionnaire and were entered and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Frequencies and percentages were used to describe descriptive data and the results were presented using tables and figures. Both binary and multivariable logistic regression analyses were conducted to test for association between the different variables. Results: A total of 306 caregivers were participated in the study. The majority of them 269(87.9%) defined diarrhea as the occurrence of watery or loose stool three and more times a day. Almost all caregivers but a few 297(97.1%) believed that diarrhea is a series problem of childhood. Caregivers' educational level, occupational status, and sex were significant factors associated with their knowledge about Oral Rehydration Salt and zinc (P ≤ 0.05), while occupational status was the only significant factor associated with their attitude (P ≤ 0.05). Female caregivers were found 2.8 times more practical about Oral Rehydration Salt and zinc utilization for diarrheal management compared to male counterparts (AOR = 2.875(1.319,6.263)). Similarly, employed caregivers were 2.9 times more to have good practice than unemployed caregivers (AOR = 2.927(1.533,5.587). Conclusion: There was good knowledge, attitude, and practice about Oral Rehydration Salt and zinc consumption among child caregivers in Gondar. Regular educational strategies aimed at improving child caregivers' awareness of diarrhea disease management and utilization of Oral Rehydration Salt and Zinc tablets are advised.